2020
DOI: 10.1519/jsc.0000000000003625
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Preconditioning Attenuates Rating of Perceived Exertion But Does Not Improve Maximal Oxygen Consumption or Maximal Power Output

Abstract: Brief consecutive periods of limb ischemia and reperfusion, known as ischemic preconditioning (IPC), have been reported to increase maximal power output (MPO) during cycling. However, the underlying mechanisms are unclear. Therefore, the purpose of the study was to investigate the effects of IPC on MPO, maximal oxygen consumption (V Ȯ2 max), muscle oxygenation, and rating of perceived exertion (RPE) during an incremental cycling test. Fourteen healthy young men participated in this double-blinded, randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 34 publications
5
13
0
Order By: Relevance
“…These findings indicated that IPC minimized the perceived exertion during isokinetic eccentric exercise, despite no influence on the attenuation of force impairment after exercise. In line with this finding, a recent study 40 verified that IPC attenuates perceived exertion but without improvements in performance. These results, together with the smaller muscle soreness observed in the present study, indicate that IPC may influence the perceptual responses to exercise.…”
Section: Discussionsupporting
confidence: 62%
“…These findings indicated that IPC minimized the perceived exertion during isokinetic eccentric exercise, despite no influence on the attenuation of force impairment after exercise. In line with this finding, a recent study 40 verified that IPC attenuates perceived exertion but without improvements in performance. These results, together with the smaller muscle soreness observed in the present study, indicate that IPC may influence the perceptual responses to exercise.…”
Section: Discussionsupporting
confidence: 62%
“…(5 min arterial occlusion, 5 min without arterial occlusion) (n = 13) [10,13,15,19,30,32,33,35,37,40,[42][43][44], eight cycles of ischemia-reperfusion (5 min arterial occlusion, 5 min without arterial occlusion) (n = 1) [44].…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…Additionally, six studies conducted the running GXT [10,13,32,35,39,42], and seven studies conducted the cycling GXT [15,30,31,33,34,37,38].…”
Section: Exercise Testsmentioning
confidence: 99%
See 2 more Smart Citations